CIK-augmented anti-PD1/CTLA4 immunotherapy eradicates chemo-resistant ovarian cancer via tripartite mechanistic synergy - Chen, Peifang; Pan, Jianrong; Chen, Ling; Feng, Xiushan (Frontiers in Oncology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) combined with adoptive cell therapy represent promising strategies against ovarian cancer, yet their synergistic mechanisms remain underexplored. This study evaluated the therapeutic efficacy of Nivolumab/Ipilimumab plus Cytokine-Induced Killer (CIK) cells in ovarian carcinoma models.MethodsHuman ovarian cancer cells (A2780/SKOV3) were subjected to three treatment conditions: untreated controls, dual immune checkpoint inhibitors (ICIs: 4 μg/mL Nivolumab + 4 μg/mL Ipilimumab), or ICIs combined with CIK cells (5×104 cells/insert), with functional impacts evaluated through comprehensive assays including CCK-8 proliferation, transwell invasion, Annexin V-FITC/PI apoptosis detection, propidium iodide-based cell cycle analysis, and quantitative wound healing migration assessment.ResultsThe triple-combination therapy demonstrated synergistic efficacy, significantly reducing SKOV3 cell proliferation by 62.3% (P<0.001) and suppressing invasion capacity by 71.5% (P<0.01) in matrigel-transwell assays. Concurrently, it induced substantial apoptosis in A2780 cells (3.2-fold increase, 22.8% vs 7.1% control), triggered pronounced G0/G1 phase arrest in SKOV3 (55% vs 40% control) with concomitant S-phase depletion, and inhibited wound closure capacity by 64.7% in combinatorial treatment groups.ConclusionThe triple-combination therapy synergistically enhances antitumor efficacy through potent G1/S checkpoint blockade, selective cytotoxicity against ICI-resistant populations, and migration-inhibitory activity, thus establishing CIK-ICI coadministration as a clinically translatable strategy for advanced ovarian malignancies.